الصورة الذهنیة لبنک المعرفة المصرى - د. محمد سعید محمد سعید (المجلة الدولية لعلوم المكتبات والمعلومات)
The study aims at identifying the extent to which the Egyptian KnowledgeBank has been used by a sample of the Egyptian society. It also aims to monitorthe emotional and cognitive aspect of the cognitive bank of the knowledge bankas well as monitor the sources of mental image formation. The study was appliedto a sample of the following categories: - University students - school teachers -school students - club attendants) in four governorates: Cairo, Alexandria,Gharbia, Assiut. The main findings of the study were that 67.72% Both theemotional side And the knowledge of the mental image of the EgyptianKnowledge Bank.The main recommendations of this study were as follows:1. The Ministry of Education should include how to use the knowledge bankwithin the content of the curriculum (library education) for primary schoolstudents in order to learn from a young age to research it and get used tousing it2. Knowledge Bank officials should allow Egyptians abroad to use theKnowledge Bank, even for a fee.3. Knowledge Bank officials should conduct training courses on how to usethe knowledge bank and its benefits to various government departmentsand not only conduct courses in universities and schools